Design the Effectiveness of Various Temperature and Humidity Sensors for Outdor - Rurono, Sastro; Sunardi, Sunardi (Signal and Image Processing Letters, 2023)
Effectiveness is a condition that shows the level of success or achievement of goals measured by quality, quantity, and time in accordance with what has been planned before. The temperature sensor measures the amount of hot / cold energy produced by the object so that it is possible to know or detect the symptoms of temperature changes in the form of analog or digital outputs. A humidity sensor is a measuring instrument to assist in the process of measuring or defining the humidity of water vapor contained in the air. This study used three categories of low price, standard, and expensive. The sensors used are temperature and humidity sensors, namely DHT11, DHT21, and DHT22 which are tested at three different times namely morning, afternoon, and night outdoors, as well as in extreme hot temperature conditions using irons and extreme cold temperature conditions using ice cubes inserted into containers.  This study used a thermohygrometer as a comparison to determine the accuracy of the sensor. After taking data at three different times, namely morning, afternoon, and night outdoors and in extreme hot temperature conditions using irons and extreme cold conditions using ice cubes 30 times, the results obtained were DHT22 sensors with expensive categories whose effectiveness was better than DHT11 sensors and DHT21 sensors. Data from DHT11 morning difference in average temperature (T) = 0.70°C and humidity (H) = 20%, day 1.2°C and 10%, and night 0.70°C and 22%, as well as extreme heat 2.50°C and 4% and extreme cold temperatures average 0.50°C and 15%. The DHT21 sensor in the morning showed an average difference of 0.20°C and 12%, afternoon differences of 0.80°C and 15%, and night 0.30°C and 10%, as well as extreme heat of 0.90°C and 12% and extreme cold of 4.30°C and 4%. DHT22 sensor in morning difference of 0.10°C and 9%, afternoon 0.60°C and 15%, and night 0.10°C and 13%, as well as extreme heat 0.30°C and 12% and extreme cold temperature of 4°C and 2.50% compared to thermohygrometer.